New Generalized Algorithm for Developing k-Step Higher Derivative Block Methods for Solving Higher Order Ordinary Differential Equations - Adeyeye, Oluwaseun; Omar, Zurni (Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
This article presents a new generalized algorithm for developing k-step (m+1) derivative block methods for solving mth order ordinary differential equations. This new algorithm utilizes the concept from the conventional Taylor series approach of developing linear multistep methods.Certain examples are given to show the simplicity involved in the usage of this new generalized algorithm.